Lithium ion battery

By adjusting the particle size distribution of the positive electrode active material and the residual carbon amount of graphite negative electrode material, the structure of lithium iron phosphate batteries is solved, and the energy density and high temperature performance of lithium iron phosphate batteries are achieved. promote.

CN119208701APending Publication Date: 2024-12-27EVE POWER CO LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411375355.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The theoretical capacity of lithium iron phosphate batteries is relatively low and have poor conductivity, which cannot meet the demand for high energy density of long-range electric vehicles, and the discharge performance becomes worse in high temperature environments.

Method used

By adjusting the proportion of positive electrode active materials with different particle sizes, the close packing of positive electrode active materials is achieved, combined with the moderate residual carbon amount of graphite negative electrode material and the heat treatment process, the structure and performance of positive electrode and negative electrode materials are optimized, and the rate of lithium ion embedding and removal are improved. and rate performance.

Benefits of technology

It significantly improves the energy density and high-temperature performance of lithium batteries, enhances the dynamics and cycling performance of lithium batteries, and achieves a volume energy density of 420-490Wh/L, improving high-temperature resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005070542530000121
    Figure BDA0005070542530000121
Patent Text Reader

Abstract

The invention specifically discloses a lithium ion battery. The lithium ion battery comprises a positive plate and a negative plate, the positive plate comprises a positive active material, and the positive active material is in four-stage grain composition and comprises first-stage grains, second-stage grains, third-stage grains and fourth-stage grains; the primary particle size R1 of the first-stage particles is smaller than 100 nm, and the first-stage particles account for 5%-30% of the positive electrode active material; the primary particle size R2 of the second-stage particles is more than or equal to 100nm and less than 400nm, and the proportion of the second-stage particles in the positive electrode active material is 10-50%; the primary particle size R3 of the third-stage particles is greater than or equal to 400 nm and less than 1000 nm, and the third-stage particles account for 5-30% of the positive electrode active material; the primary particle size R4 of the fourth-stage particles is larger than or equal to 1000 nm and smaller than or equal to 4000 nm, and the fourth-stage particles account for 5%-20% of the positive electrode active material; the negative plate comprises a graphite negative electrode material, the residual carbon content of the surface of the graphite negative electrode material is 0-5%, and the graphitization degree of the graphite negative electrode material is 90-97%. The method has the advantage of improving the energy density and high-temperature performance of the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium ion battery. Background Art

[0002] Under the pressure of energy crisis and environmental pollution, safety, environmental protection and energy saving have become the themes of today's automobile development. New energy vehicles are highly valued and strongly supported by the transportation and energy departments due to their advantages of energy saving, environmental protection and pollution-free. Lithium batteries, as the key to new energy vehicles, play a very important role in them. With the continuous development of the new energy field, the performance requirements for lithium batteries are getting higher and higher.

[0003] As a positive electrode material for lithium-ion batteries, lithium iron phosphate has abundant raw material sources, high theoretical capacity, stable structure, good safety performance and environmental friendliness. It is the most promising positive electrode material that can be widely used in the field of energy storage and power batteries in the future. However, the theoretical capacity of lithium iron phosphate material is relatively low (about 170mAh / g), and its conductivity is poor, which is not conducive to the improvement of lithium battery energy density and rate performance, and cannot meet the demand for high energy density of long-range electric vehicles; in addition, the discharge performance of lithium iron phosphate batteries deteriorates in high temperature environments. Therefore, it is urgent to provide a lithium iron phosphate battery with both high energy density and high temperature performance. Summary of the invention

[0004] In order to improve the energy density and high temperature performance of a lithium iron phosphate battery, the present invention provides a lithium ion battery.

[0005] The present invention provides a lithium ion battery, which adopts the following technical solution:

[0006] A lithium-ion battery, comprising a positive electrode sheet and a negative electrode sheet; the positive electrode sheet comprises a positive electrode active material, the positive electrode active material is a four-level particle gradation, including first-level particles, second-level particles, third-level particles and fourth-level particles; the primary particle size R1 of the first-level particles satisfies R1<100nm, and the number of the first-level particles in the positive electrode active material accounts for 5%-30%; the primary particle size R2 of the second-level particles satisfies 100nm≤R2<400nm, and the number of the second-level particles in the positive electrode active material accounts for 10%-50%; the primary particle size R3 of the third-level particles satisfies 400nm≤R3<1000nm, and the number of the third-level particles in the positive electrode active material accounts for 5%-30%; the primary particle size R4 of the fourth-level particles satisfies 1000nm≤R4≤4000nm, and the number of the fourth-level particles in the positive electrode active material accounts for 5%-20%; the surface density of the positive electrode sheet is 180-350g / m 2The compaction density of the positive electrode is 2.45-2.85g / cm 3 ; The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a graphite negative electrode material; the residual carbon content on the surface of the graphite negative electrode material is 0%-5%, and the degree of graphitization of the graphite negative electrode material is 90%-97%; the gram capacity of the negative electrode sheet is 345-365mAh / g.

[0007] Carbon residue refers to the amount of carbon residue left after a substance evaporates or decomposes under specific conditions.

[0008] First, by adjusting the proportion of positive electrode active materials with different particle sizes, the positive electrode active materials can be densely stacked. In this state, the particle size distribution of the lithium supplement and the positive electrode active materials can be adjusted to be consistent, which not only helps to increase the rate of lithium ion insertion and extraction in the positive electrode sheet and improve the kinetic performance of the lithium battery, but also can achieve an ideal electrode sheet compaction density, which is beneficial to reduce the thickness of the positive electrode sheet and improve the energy density of the lithium battery; specifically, in the same type of lithium battery, the positive electrode sheet of the present invention is used, and the mass of the positive electrode active material in the lithium battery is significantly increased (for lithium batteries with wound-type batteries, the overall thickness of the positive electrode sheet becomes thinner, and the number of positive electrode sheets that can be wound increases. Accordingly, the length of the positive electrode sheet that can be stored in the winding core increases, and the energy density of the lithium battery increases; for lithium batteries with stacked-type batteries, the overall thickness of the positive electrode sheet becomes thinner, and the number of positive electrode sheets that can be stacked in the lithium battery increases, and accordingly, the energy density of the lithium battery increases), thereby helping to improve the energy density of the lithium battery and obtain a lithium battery with a volume energy density of 420-490Wh / L.

[0009] Second, by adjusting the amount of residual carbon on the surface of the graphite negative electrode material, the residual carbon helps to improve the degree of graphitization of the graphite negative electrode material, which can not only increase the desolvation rate of lithium ions at the interface of the electrode and the electrolyte, enhance the desolvation ability, but also improve the high temperature resistance of the lithium battery; and, the particle size of the positive electrode active material in the present invention is matched so that the positive electrode active material has a suitable specific surface area, and a distance is formed in the positive electrode sheet that is conducive to the diffusion of the lithium battery, thereby adjusting the charge and discharge rate of the positive electrode to match the above-mentioned graphite negative electrode material, avoiding the occurrence of lithium precipitation at the negative electrode, which helps to improve the rate performance and cycle performance of the lithium battery.

[0010] Preferably, the residual carbon content on the surface of the graphite negative electrode material is 0.1%-3.5%.

[0011] By further optimizing the amount of residual carbon on the negative electrode surface, the internal resistance of the negative electrode sheet can be reduced, which helps to further improve the cycle performance and high temperature resistance of the lithium battery.

[0012] Preferably, the negative electrode active material is prepared by a method comprising the following steps: mixing graphite and a coating agent and then performing a first heat treatment, and performing a second heat treatment after the first heat treatment to obtain the graphite negative electrode material.

[0013] Preferably, the coating agent includes asphalt, and the graphite includes artificial graphite; the temperature of the first heat treatment is 2800-3000°C, and the time of the first heat treatment is 60-100h; the temperature of the second heat treatment is 800-1600°C, and the time of the second heat treatment is 3-10h; a graphite negative electrode material with a residual carbon content of 0.3%-2.0% and a degree of graphitization of 93%-96% is obtained.

[0014] By selecting asphalt as a coating agent, after heat treatment, defects such as holes, grooves, cracks in graphite can be modified, thereby improving the electrochemical reversible capacity and cycle performance of graphite. In addition, asphalt as a coating agent can play a positive role in regulating the amount of residual carbon on the surface of graphite. Moreover, asphalt is low in cost and the raw materials are easily available, which can reduce production costs.

[0015] Preparing graphite negative electrode materials by first high-temperature heat treatment and then low-temperature heat treatment can promote the complete development of graphite microcrystals, increase the degree of graphitization of the material, increase the spacing between graphite sheets, and facilitate the rapid insertion and extraction of lithium ions, thereby helping to improve the kinetic and electrochemical properties of lithium batteries.

[0016] Preferably, the compaction density of the positive electrode active material is 2.45-2.75 g / cm 3 .

[0017] The compaction density of the positive electrode active material in the present invention is controlled within the above range, which helps to increase the energy per unit volume of the battery and improve the energy density of the lithium battery.

[0018] Preferably, the positive electrode active material includes lithium iron phosphate.

[0019] Preferably, the surface density of the positive electrode sheet is 200-350 g / m 2 , and / or, the compaction density of the positive electrode sheet is 2.55-2.85g / m 3 .

[0020] The present invention controls the surface density and compaction density of the positive electrode active material, adjusts the surface density and compaction density of the positive electrode active material layer, and controls the porosity in the positive electrode active material layer within a certain range, thereby forming a pore structure that is beneficial to lithium ion transmission in the positive electrode active material layer, so that the lithium ion extraction rate at the positive electrode can be balanced with the lithium ion embedding rate at the negative electrode, thereby avoiding the occurrence of lithium precipitation at the negative electrode, and improving the cycle performance and rate performance of the lithium battery.

[0021] Preferably, the volume energy density of the lithium battery is 460-480Wh / L.

[0022] Preferably, the CB value of the lithium battery is 1.1-1.4.

[0023] By controlling the CB value within the above range, the compatibility of the positive electrode active material and the negative electrode active material can be adjusted, thereby avoiding the phenomenon of lithium precipitation during the cycle of the lithium battery and improving the cycle performance of the lithium battery. DETAILED DESCRIPTION

[0024] For better understanding and implementation, the technical solution of the present invention will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0026] Unless otherwise indicated, all numerical values ​​expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.

[0027] As used herein, "and / or" means one or all of the mentioned elements.

[0028] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.

[0029] All percentages in the present invention are by weight, unless otherwise specified.

[0030] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.

[0031] Example 1

[0032] 1. Preparation of negative electrode active materials

[0033] The graphite and asphalt were mixed and then heat treated at 2900°C for 80 hours, and then heat treated at 1200°C for 7 hours to obtain a graphite negative electrode material with a residual carbon content of 3%.

[0034] 2. Preparation of positive electrode active materials

[0035] The positive electrode active material (lithium iron phosphate) is divided into first-level particles, second-level particles, third-level particles and fourth-level particles according to particle size;

[0036] The primary particle size R1 of the first-level particles satisfies R1<100nm, and the number of the first-level particles in the positive electrode active material accounts for 20%; the primary particle size R2 of the second-level particles satisfies 100nm≤R2<400nm, and the number of the second-level particles in the positive electrode active material accounts for 40%; the primary particle size R3 of the third-level particles satisfies 400nm≤R3<1000nm, and the number of the third-level particles in the positive electrode active material accounts for 30%; the primary particle size R4 of the fourth-level particles satisfies 1000nm≤R4≤4000nm, and the number of the fourth-level particles in the positive electrode active material accounts for 10%;

[0037] The positive electrode active materials with different particle size distributions are mixed to obtain the positive electrode active materials.

[0038] 3. Negative electrode preparation

[0039] The graphite negative electrode material, the conductive agent acetylene black, the thickener CMC, and the binder SBR are added to a vacuum mixer at a mass ratio of 96.4:1:1.2:1.4 for mixing, and then deionized water is added to the mixture, and the mixed slurry is stirred to a uniform state under the action of the vacuum mixer, thereby obtaining the negative electrode slurry of this embodiment;

[0040] The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature and then transferred to an oven for further drying. After drying in the oven, a negative electrode sheet semi-finished product is obtained, and then the negative electrode sheet semi-finished product is cold pressed and cut to obtain the negative electrode sheet to be assembled.

[0041] 4. Preparation of positive electrode

[0042] The lithium iron phosphate positive electrode active material, the conductive agent (acetylene black), and polyvinylidene fluoride PVDF (molecular weight 500000Da) were added into a vacuum mixer at a mass ratio of 97.9:0.9:1.2 for mixing, and then the solvent NMP was added into the mixed slurry, and the mixed slurry was stirred into a uniform state under the action of the vacuum mixer, thereby obtaining the positive electrode slurry of this embodiment;

[0043] The positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, and then transferred to an oven for further drying. After drying in the oven, a positive electrode sheet semi-finished product is obtained, and then the positive electrode sheet semi-finished product is cold pressed and cut to obtain the positive electrode sheet to be assembled (the surface density of the positive electrode sheet is 310g / cm 3, compacted density is 2.83g / cm 3 ).

[0044] 5. Lithium battery assembly

[0045] A commercially available polyethylene film is used as a separator of a lithium-ion battery, and a commercially available electrolyte suitable for a 4.2V (charging upper limit) voltage system battery is used. The positive electrode sheet, the negative electrode sheet (CB value is 1.14) and the separator are wound together to obtain a bare cell, and the bare cell is packaged, injected, left to stand, formed, and divided to obtain a finished battery.

[0046] Example 2

[0047] 1. Preparation of negative electrode active materials

[0048] The graphite and asphalt were mixed and then heat treated at 2800°C for 100 hours, and then heat treated at 1600°C for 3 hours to obtain a graphite negative electrode material with a residual carbon content of 0.5%.

[0049] 2. Preparation of positive electrode active materials

[0050] The positive electrode active material (lithium iron phosphate) is divided into first-level particles, second-level particles, third-level particles and fourth-level particles according to particle size;

[0051] The primary particle size R1 of the first-level particles satisfies R1<100nm, and the number of the first-level particles in the positive electrode active material accounts for 10%; the primary particle size R2 of the second-level particles satisfies 100nm≤R2<400nm, and the number of the second-level particles in the positive electrode active material accounts for 40%; the primary particle size R3 of the third-level particles satisfies 400nm≤R3<1000nm, and the number of the third-level particles in the positive electrode active material accounts for 30%; the primary particle size R4 of the fourth-level particles satisfies 1000nm≤R4≤4000nm, and the number of the fourth-level particles in the positive electrode active material accounts for 20%;

[0052] The positive electrode active materials with different particle size distributions are mixed to obtain the positive electrode active materials.

[0053] 3. Negative electrode preparation

[0054] The graphite negative electrode material, the conductive agent acetylene black, the thickener CMC, and the binder SBR are added to a vacuum mixer at a mass ratio of 96.4:1:1.2:1.4 for mixing, and then deionized water is added to the mixture, and the mixed slurry is stirred to a uniform state under the action of the vacuum mixer, thereby obtaining the negative electrode slurry of this embodiment;

[0055] The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, and then transferred to an oven for further drying. After drying in the oven, a negative electrode sheet semi-finished product is obtained, and then the negative electrode sheet semi-finished product is cold pressed and cut to obtain the negative electrode sheet to be assembled.

[0056] 4. Preparation of positive electrode

[0057] The lithium iron phosphate positive electrode active material, the conductive agent (acetylene black), and polyvinylidene fluoride PVDF (molecular weight 500000Da) were added into a vacuum mixer at a mass ratio of 97.9:0.9:1.2 for mixing, and then the solvent NMP was added into the mixed slurry, and the mixed slurry was stirred into a uniform state under the action of the vacuum mixer, thereby obtaining the positive electrode slurry of this embodiment;

[0058] The positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, and then transferred to an oven for further drying. After drying in the oven, a positive electrode sheet semi-finished product is obtained, and then the positive electrode sheet semi-finished product is cold pressed and cut to obtain the positive electrode sheet to be assembled (the surface density of the positive electrode sheet is 300g / cm 3 , compacted density is 2.85g / cm 3 ).

[0059] 5. Lithium battery assembly

[0060] A commercially available polyethylene film is used as a separator of a lithium-ion battery, and a commercially available electrolyte suitable for a 4.2V (charging upper limit) voltage system battery is used. The positive electrode sheet, the negative electrode sheet (CB value is 1.11) and the separator are wound together to obtain a bare cell, and the bare cell is packaged, injected, left to stand, formed, and divided to obtain a finished battery.

[0061] Example 3

[0062] 1. Preparation of negative electrode active materials

[0063] The graphite and asphalt were mixed and then heat treated at 3000°C for 60 hours, and then heat treated at 800°C for 10 hours to obtain a graphite negative electrode material with a residual carbon content of 5%.

[0064] 2. Preparation of positive electrode active materials

[0065] The positive electrode active material (lithium iron phosphate) is divided into first-level particles, second-level particles, third-level particles and fourth-level particles according to particle size;

[0066] The primary particle size R1 of the first-level particles satisfies R1<100nm, and the number of the first-level particles in the positive electrode active material accounts for 30%; the primary particle size R2 of the second-level particles satisfies 100nm≤R2<400nm, and the number of the second-level particles in the positive electrode active material accounts for 50%; the primary particle size R3 of the third-level particles satisfies 400nm≤R3<1000nm, and the number of the third-level particles in the positive electrode active material accounts for 15%; the primary particle size R4 of the fourth-level particles satisfies 1000nm≤R4≤4000nm, and the number of the fourth-level particles in the positive electrode active material accounts for 5%;

[0067] The positive electrode active materials with different particle size distributions are mixed to obtain the positive electrode active materials.

[0068] 3. Negative electrode preparation

[0069] The graphite negative electrode material, the conductive agent acetylene black, the thickener CMC, and the binder SBR are added to a vacuum mixer at a mass ratio of 96.4:1:1.2:1.4 for mixing, and then deionized water is added to the mixture, and the mixed slurry is stirred to a uniform state under the action of the vacuum mixer, thereby obtaining the negative electrode slurry of this embodiment;

[0070] The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, and then transferred to an oven for further drying. After drying in the oven, a negative electrode sheet semi-finished product is obtained, and then the negative electrode sheet semi-finished product is cold pressed and cut to obtain the negative electrode sheet to be assembled.

[0071] 4. Preparation of positive electrode

[0072] The lithium iron phosphate positive electrode active material, the conductive agent (acetylene black), and polyvinylidene fluoride PVDF (molecular weight 500000Da) were added into a vacuum mixer at a mass ratio of 97.9:0.9:1.2 for mixing, and then the solvent NMP was added into the mixed slurry, and the mixed slurry was stirred into a uniform state under the action of the vacuum mixer, thereby obtaining the positive electrode slurry of this embodiment;

[0073] The positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, and after drying at room temperature, it is transferred to an oven for further drying. After drying in the oven, a positive electrode semi-finished product is obtained, and then the positive electrode semi-finished product is cold pressed and cut to obtain the positive electrode sheet to be assembled (the surface density of the positive electrode sheet is 315g / cm 3 , compacted density is 2.82g / cm 3 ).

[0074] 5. Lithium battery assembly

[0075] A commercially available polyethylene film is used as a separator of a lithium-ion battery, and a commercially available electrolyte suitable for a 4.2V (charging upper limit) voltage system battery is used as an electrolyte. The above-mentioned positive electrode sheet, negative electrode sheet (CB value is 1.19) and separator are wound together to obtain a bare cell, and the bare cell is packaged, injected, left to stand, formed, and divided to obtain a finished battery.

[0076] Example 4

[0077] 1. Preparation of negative electrode active materials

[0078] The graphite and asphalt were mixed and then heat treated at 3000°C for 60 hours, and then heat treated at 1000°C for 5 hours to obtain a graphite negative electrode material with a residual carbon content of 2%.

[0079] 2. Preparation of positive electrode active materials

[0080] The positive electrode active material (lithium iron phosphate) is divided into first-level particles, second-level particles, third-level particles and fourth-level particles according to particle size;

[0081] The primary particle size R1 of the first-level particles satisfies R1<100nm, and the number of the first-level particles in the positive electrode active material accounts for 25%; the primary particle size R2 of the second-level particles satisfies 100nm≤R2<400nm, and the number of the second-level particles in the positive electrode active material accounts for 25%; the primary particle size R3 of the third-level particles satisfies 400nm≤R3<1000nm, and the number of the third-level particles in the positive electrode active material accounts for 30%; the primary particle size R4 of the fourth-level particles satisfies 1000nm≤R4≤4000nm, and the number of the fourth-level particles in the positive electrode active material accounts for 20%;

[0082] The positive electrode active materials with different particle size distributions are mixed to obtain the positive electrode active materials.

[0083] 3. Negative electrode preparation

[0084] The graphite negative electrode material, the conductive agent acetylene black, the thickener CMC, and the binder SBR are added to a vacuum mixer at a mass ratio of 96.4:1:1.2:1.4 for mixing, and then deionized water is added to the mixture, and the mixed slurry is stirred to a uniform state under the action of the vacuum mixer, thereby obtaining the negative electrode slurry of this embodiment;

[0085] The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, and then transferred to an oven for further drying. After drying in the oven, a negative electrode sheet semi-finished product is obtained, and then the negative electrode sheet semi-finished product is cold pressed and cut to obtain the negative electrode sheet to be assembled.

[0086] 4. Preparation of positive electrode

[0087] The lithium iron phosphate positive electrode active material, the conductive agent (acetylene black), and polyvinylidene fluoride PVDF (molecular weight 500000Da) were added into a vacuum mixer at a mass ratio of 97.9:0.9:1.2 for mixing, and then the solvent NMP was added into the mixed slurry, and the mixed slurry was stirred into a uniform state under the action of the vacuum mixer, thereby obtaining the positive electrode slurry of this embodiment;

[0088] The positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, and after drying at room temperature, it is transferred to an oven for further drying. After drying in the oven, a positive electrode semi-finished product is obtained, and then the positive electrode semi-finished product is cold pressed and cut to obtain the positive electrode sheet to be assembled (the surface density of the positive electrode sheet is 305g / cm 3 , compacted density is 2.83g / cm 3 ).

[0089] 5. Lithium battery assembly

[0090] A commercially available polyethylene film is used as a separator of a lithium-ion battery, and a commercially available electrolyte suitable for a 4.2V (charging upper limit) voltage system battery is used. The positive electrode sheet, the negative electrode sheet (CB value is 1.15) and the separator are wound together to obtain a bare cell, and the bare cell is packaged, injected, left to stand, formed, and divided to obtain a finished battery.

[0091] Example 5

[0092] The difference between this embodiment and embodiment 1 is that, in the preparation process of the graphite negative electrode material, an equal weight of resin is used to replace the asphalt used in embodiment 1, and the other steps and parameter settings are consistent with embodiment 1.

[0093] Example 6

[0094] The difference between this embodiment and embodiment 1 is that, during the preparation process of the graphite negative electrode material, the temperature in the two heat treatment processes is always maintained at 2300°C for 60 hours, followed by heat treatment at 300°C for 5 hours; the other steps and parameter settings are consistent with embodiment 1.

[0095] Comparative Example 1

[0096] The difference between this comparative example and Example 1 is that the particle size D of the positive electrode active material satisfies 50nm<D<1500nm, and the positive electrode active material is not subjected to particle grading; the negative electrode active material is artificial graphite (residual carbon content 10%); and the other steps and parameter settings are consistent with Example 1.

[0097] Comparative Example 2

[0098] The difference between this comparative example and Example 1 is that the particle size distribution of the positive electrode active material is different. Specifically, the positive electrode active material includes first-stage particles, second-stage particles and third-stage particles;

[0099] The primary particle size R1 of the first-level particles satisfies R1<300nm, and the number of first-level particles in the positive electrode active material accounts for 35%-45%; the primary particle size R2 of the second-level particles satisfies 300nm≤R2<1700nm, and the number of second-level particles in the positive electrode active material accounts for 45%-65%; the primary particle size R3 of the third-level particles satisfies 1700nm≤R3≤4000nm, and the number of third-level particles in the positive electrode active material accounts for <10%; other steps and parameter settings are consistent with Example 1.

[0100] Comparative Example 3

[0101] The difference between this comparative example and Example 1 is that the particle size distribution of the positive electrode active material is different. Specifically, the positive electrode active material includes first-level particles, second-level particles, third-level particles, fourth-level particles and fifth-level particles;

[0102] The primary particle size R1 of the first-level particles satisfies R1<100nm, and the number of first-level particles in the positive electrode active material accounts for 30%-35%; the primary particle size R2 of the second-level particles satisfies 100nm≤R2<300nm, and the number of second-level particles in the positive electrode active material accounts for 25%-30%; the primary particle size R3 of the third-level particles satisfies 300nm≤R3<600nm, and the number of third-level particles in the positive electrode active material accounts for 25%-30%; the primary particle size R4 of the fourth-level particles satisfies 600nm≤R4<1200nm, and the number of fourth-level particles in the positive electrode active material accounts for 5%-15%; the primary particle size R5 of the fifth-level particles satisfies 1200nm≤R5≤4000nm, and the number of fifth-level particles in the positive electrode active material accounts for <5%; other steps and parameter settings are consistent with Example 1.

[0103] Comparative Example 4

[0104] The difference between this embodiment and embodiment 1 is that the particle size distribution of the positive electrode active material is different, specifically:

[0105] The primary particle size R1 of the first-level particles satisfies R1<200nm, and the number of first-level particles in the positive electrode active material accounts for 15%-20%; the primary particle size R2 of the second-level particles satisfies 200nm≤R2<450nm, and the number of second-level particles in the positive electrode active material accounts for 35%-45%; the primary particle size R3 of the third-level particles satisfies 500nm≤R3≤700nm, and the number of third-level particles in the positive electrode active material accounts for 30%-45%; the primary particle size R4 of the fourth-level particles satisfies R4>1200nm, and the number of fourth-level particles in the positive electrode active material accounts for <8%; other steps and parameter settings are consistent with Example 1.

[0106] Test Method

[0107] 1. Volume energy density test

[0108] At 25°C, the battery is charged at a constant current of 0.5C to 3.75V, then charged at a constant voltage until the current drops to 0.05C, and then discharged at a constant current of 0.5C to 2.0V to obtain the discharge energy; volume energy density = discharge energy / battery volume.

[0109] 2. High temperature performance test

[0110] At 25°C, the battery was charged to 3.75V at a constant current of 1C, and then charged at a constant voltage until the current dropped to 0.05C. The battery was then transferred to a 60°C oven for storage for 30 days. After the battery cooled to room temperature, it was discharged to 2.0V at a constant current of 1C. The capacity retention rate was calculated by comparing the obtained discharge capacity with the discharge capacity before high-temperature storage; capacity retention rate = discharge capacity after high-temperature storage / discharge capacity before high-temperature storage × 100%;

[0111] The battery was then charged at a constant current of 1C to 3.75V, then charged at a constant voltage until the current dropped to 0.05C, and then discharged at a constant current of 1C to 2.0V. The discharge capacity obtained was compared with the discharge capacity before high-temperature storage to obtain the capacity recovery rate; that is, capacity recovery rate = discharge capacity after charging and discharging again after high-temperature storage / discharge capacity before high-temperature storage × 100%.

[0112] 3. Carbon Residue Test

[0113] In the following examples and comparative examples, residual carbon amount = coking value × addition amount.

[0114] Test method for coking value: Weigh 1.0000g of dry sample with a particle size of 1-3mm, place it in a 20ml porcelain crucible with constant weight, cover it, and place it in a 100mL porcelain crucible or graphite crucible pre-paved with 10mm thick coke particles, then fill the gap between the two crucibles with coke particles, bury the crucible completely in the coke particles, and cover the outer crucible cover. Place the crucible on a nickel-chromium wire support and put it in a 550℃±l0℃ muffle furnace with the bottom of the crucible about 25mm away from the bottom of the furnace. After the sample is placed in, the furnace temperature must be restored to a constant temperature within 10min, and continue heating for 2h. Take out the crucible and cool it in the air for about 15min, take out the inner crucible, sweep away the coke powder attached to the outside of the crucible, put it in a dryer, cool to room temperature, and weigh it. The coking value is calculated according to the following formula:

[0115] K(%)=(m1-m2) / m×100%;

[0116] Wherein: K is the coking value of asphalt / %; m is the mass of sample / g; m1 is the mass of inner crucible / g; m2 is the mass of inner crucible and residue / g.

[0117] 4. Particle size test

[0118] The particle size of the positive electrode active material is tested by the following method: SEM test is performed on the positive electrode active material, 3-10 pictures are randomly taken at a resolution of 20K, the size and quantity of the positive electrode active material in each picture are marked, and the particle size of each level of positive electrode active material and the quantity ratio of each level of positive electrode active material are calculated.

[0119] Table 1

[0120]

[0121] In combination with Examples 1-4, Comparative Examples 1-4 and Table 1, it can be seen that the distribution and proportion of particle size will affect the high temperature performance of the battery. The present invention adopts first-level particles, second-level particles, third-level particles and fourth-level particles with the above-mentioned particle size range, and controls the number proportion of each of them in the positive electrode active material, so that the positive electrode active material can achieve a good stacking density without the action of external high voltage, which is helpful to improve the insertion and extraction rate of lithium ion batteries and improve the kinetic performance of lithium batteries; and the residual carbon content of the negative electrode active material used in the negative electrode sheet is controlled within a suitable range. At this time, the positive electrode sheet can cooperate with the negative electrode sheet, which can not only balance the transfer of lithium ions between the positive and negative electrodes, but also help to exert the gram capacity of the positive and negative electrodes, and help to improve the capacity of the lithium battery. At the same time, the positive electrode active material with the above-mentioned particle size distribution and proportion can reduce the thickness of the active material layer on the surface of the positive electrode sheet to a certain extent. For a battery core structure with a fixed size, the number of stacked layers of the positive electrode sheet increases or the number of windings increases, which is conducive to improving the volume energy density of the lithium battery.

[0122] In combination with Example 1, Examples 5-6 and Table 1, it can be seen that the selection of the coating agent and the setting of the heat treatment temperature during the preparation of the negative electrode will have an impact on the negative electrode, especially a negative effect on the kinetic properties of the negative electrode, and affect the high temperature capacity retention rate and high temperature capacity recovery rate of the battery.

[0123] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A lithium ion battery, characterized in that: Including positive electrode sheet and negative electrode sheet; The positive electrode sheet includes a positive electrode active material, and the positive electrode active material has a four-level particle gradation, including first-level particles, second-level particles, third-level particles and fourth-level particles; The primary particle size R1 of the first-level particles satisfies R1<100nm, and the number of the first-level particles in the positive electrode active material accounts for 5%-30%; the primary particle size R2 of the second-level particles satisfies 100nm≤R2<400nm, and the number of the second-level particles in the positive electrode active material accounts for 10%-50%; the primary particle size R3 of the third-level particles satisfies 400nm≤R3<1000nm, and the number of the third-level particles in the positive electrode active material accounts for 5%-30%; the primary particle size R4 of the fourth-level particles satisfies 1000nm≤R4≤4000nm, and the number of the fourth-level particles in the positive electrode active material accounts for 5%-20%; The surface density of the positive electrode sheet is 180-350g / m 2 The compaction density of the positive electrode is 2.45-2.85g / cm 3 ; The negative electrode sheet comprises a negative electrode active material, and the negative electrode active material comprises a graphite negative electrode material; the residual carbon content on the surface of the graphite negative electrode material is 0%-5%, and the graphitization degree of the graphite negative electrode material is 90%-97%.

2. The lithium-ion battery according to claim 1, characterized in that: The residual carbon content on the surface of the graphite negative electrode material is 0.1%-3.5%.

3. The lithium-ion battery according to claim 1, characterized in that: The negative electrode active material is prepared by a method comprising the following steps: mixing graphite and a coating agent and then performing a first heat treatment, and performing a second heat treatment after the first heat treatment to obtain a graphite negative electrode material.

4. The lithium-ion battery according to claim 3, characterized in that: The coating agent includes asphalt; the temperature of the first heat treatment is 2800-3000°C, and the time of the first heat treatment is 60-100h; the temperature of the second heat treatment is 800-1600°C, and the time of the second heat treatment is 3-10h.

5. The lithium-ion battery according to claim 1, characterized in that: The compaction density of the positive electrode active material is 2.45-2.75 g / cm 3 .

6. The lithium-ion battery according to claim 1, characterized in that: The positive electrode active material includes lithium iron phosphate material.

7. The lithium-ion battery according to claim 1, characterized in that: The surface density of the positive electrode sheet is 200-350g / m 2 , and / or, the compaction density of the positive electrode sheet is 2.55-2.85g / m 3 .

8. The lithium-ion battery according to claim 1, characterized in that: The volume energy density of the lithium battery is 460-480Wh / L.

Citation Information

Cited By

  • Lithium-ion battery

    WO2026065751A1

  • Positive electrode sheet and lithium-ion battery using same

    WO2026157099A1

  • Battery cell, battery device and electric device

    WO2026183804A1

  • Battery cell, battery apparatus, electrical apparatus and energy storage apparatus

    WO2026200070A1

  • Battery cell, battery device, electric device and energy storage device

    WO2026201212A1